Answer:
Step-by-step explanation:
Upper box in the diamond: Add the two numbers ⇒ (-2) + 3 = -1
Bottom box in the diamond : Multiply the two numbers ⇒ (-2) * 3 = -6
3) Upper box = (-6) + (-3) = (-9)
Bottom box = (-6) *(-3) = 18
4) Upper box = 1 +(-11) = -10
Bottom box = 1 *(-11) = -11
5) Upper box = 7+8 = 15
Bottom box = 7*8 = 56
Answer:
WY= squar root 55 + 4
Step-by-step explanation:
The answer just keeps coming back to zero dude it's simple you can't really calculate this either way the value of it would just be zero you can't simplify it or anything
The answer to this is True.